2017
DOI: 10.1186/s10194-017-0759-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of headache disorders in Lithuania and their public-health and policy implications: a population-based study within the Eurolight Project

Abstract: BackgroundThe Eurolight project assessed the impact of headache disorders in ten EU countries, using the same structured questionnaire but varying sampling methods. In Lithuania, sample selection employed methods in line with consensus recommendations for population-based burden-of-headache studies.MethodsThe survey was cross-sectional. We identified, from the Residents’ Register Service, a sample of inhabitants of Kaunas city and surrounding Kaunas region reflecting age (in the range 18–65 years), gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 29 publications
3
45
0
14
Order By: Relevance
“…Studies in Georgia, 17,30 Lithuania, 19 Moldova, 18 and Russia 20,31 using standardized methodology found broadly similar results (►Table 1): 1-year prevalence of all headache disorders in the range of 53 to 75% and of migraine in the much narrower range of 16 to 20%. Except in Moldova (18%), the prevalence of TTH was consistently higher than that of migraine (31-42%).…”
Section: European Regionmentioning
confidence: 71%
See 3 more Smart Citations
“…Studies in Georgia, 17,30 Lithuania, 19 Moldova, 18 and Russia 20,31 using standardized methodology found broadly similar results (►Table 1): 1-year prevalence of all headache disorders in the range of 53 to 75% and of migraine in the much narrower range of 16 to 20%. Except in Moldova (18%), the prevalence of TTH was consistently higher than that of migraine (31-42%).…”
Section: European Regionmentioning
confidence: 71%
“…The effect was similar with all headache types in Georgia, 30 was greatest with headache on 15 days per month and, among episodic headaches, more with migraine than TTH, in Russia, 31 and was observed only with migraine and headache on 15 days per month, not TTH, in Lithuania. 19 Nearly a quarter (17.7% of males, 28% of females) of participants with migraine in Eurolight lost >10% of their productive time and nearly half (44.7% of males, 53% of females) of those with probable MOH (pMOH) lost >20%. 27 Societal impact was consequently high: the burden of indirect costs, attributable mostly to lost productivity, was equated to 1.5% lost gross domestic product (GDP) in Lithuania and to 1.8% lost GDP in Russia (►Table 2).…”
Section: European Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Eurolight project estimated that indirect costs accounted for 92% of the financial burden of TTH [ 6 ]. In fact, recent data derived from the Eurolight project have confirmed that the burden of TTH is also substantial in middle-income European countries such as Lithuania [ 7 ]. Similarly, headache burden is also similar in low-income countries, e.g., Ethiopia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%